Screen Pseudo-Slant Lightlike Submersions - S. S. Shukla; Shivam Omar (IndoMS, 2023)
In this article, we introduce the notion of screen pseudo-slant lightlike submersions from an indefinite Kähler manifold onto a lightlike manifold which includes complex (invariant), screen real (anti-invariant), screen slant and SCR lightlike submersions. We study some properties of proper screen pseudo-slant lightlike submersions with non-trivial examples and gave a characterization theorem. We also obtain integrability conditions of distributions involved in the definition of such submersions.